2020
DOI: 10.1016/j.clml.2019.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Elevated White Blood Cell Levels and Thrombotic Events in Patients With Polycythemia Vera: A Real-World Analysis of Veterans Health Administration Data

Abstract: Patients with polycythemia vera (PV) have a substantial risk of thrombotic events (TEs). In the present retrospective analysis using Veterans Health Administration claims data, 25% of 1565 patients experienced a TE during follow-up. We observed a positive, significant association between white blood cell (WBC) counts ‡ 8.5 3 10 9 /L and TE occurrence (reference, WBC count < 7.0 3 10 9 /L), supporting continued inclusion of WBC count control in disease management. Background: Patients with polycythemia vera (PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 5 publications
2
14
0
Order By: Relevance
“…24 A very similar analysis of a cohort of 1565 patients with PV from US Veterans Affairs hospitals demonstrated that patients with leukocyte counts ⩾8.5–<11 × 10 9 /l had a significantly increased risk of thrombotic events compared with those with leukocytes <7 × 10 9 /l, with the hazard ratio highest for those with leukocyte counts ⩾11 × 10 9 /l. 25 Similar findings were also reported in a time-dependent analysis of the ECLAP (European Collaboration on Low-Dose Aspirin in Polycythemia Vera) study which found, after adjusting for potential confounding factors, that patients with leukocyte counts >15 × 10 9 /l had a significantly higher risk of thrombosis compared with those with leukocyte counts <10 × 10 9 /l. 26 Consensus guidelines from the National Comprehensive Cancer Network (NCCN) in the US recognize progressive leukocytosis, along with new thrombosis or disease-related major bleeding, progressive disease-related symptoms, a frequent or persistent need for phlebotomy with poor tolerance of the same, symptomatic or progressive splenomegaly and symptomatic thrombocytosis as potential indications for initiation of cytoreductive therapy in ‘low-risk’ patients with PV.…”
Section: Updates In Risk Stratification For Thrombosis: a Role For Lesupporting
confidence: 81%
“…24 A very similar analysis of a cohort of 1565 patients with PV from US Veterans Affairs hospitals demonstrated that patients with leukocyte counts ⩾8.5–<11 × 10 9 /l had a significantly increased risk of thrombotic events compared with those with leukocytes <7 × 10 9 /l, with the hazard ratio highest for those with leukocyte counts ⩾11 × 10 9 /l. 25 Similar findings were also reported in a time-dependent analysis of the ECLAP (European Collaboration on Low-Dose Aspirin in Polycythemia Vera) study which found, after adjusting for potential confounding factors, that patients with leukocyte counts >15 × 10 9 /l had a significantly higher risk of thrombosis compared with those with leukocyte counts <10 × 10 9 /l. 26 Consensus guidelines from the National Comprehensive Cancer Network (NCCN) in the US recognize progressive leukocytosis, along with new thrombosis or disease-related major bleeding, progressive disease-related symptoms, a frequent or persistent need for phlebotomy with poor tolerance of the same, symptomatic or progressive splenomegaly and symptomatic thrombocytosis as potential indications for initiation of cytoreductive therapy in ‘low-risk’ patients with PV.…”
Section: Updates In Risk Stratification For Thrombosis: a Role For Lesupporting
confidence: 81%
“…Two recently published retrospective analyses from Parasuraman and colleagues used data from the Veterans Health Administration (VHA), the largest integrated health care system in the US, with an aim to replicate findings from CYTO-PV in a real-world population. 16,17 The 2 analyses focused independently on the effects of Hct control and WBC count on the risk of a thrombotic event in patients with PV.…”
Section: Blood Cell Counts and Thrombotic Events In The Veteran Popul...mentioning
confidence: 99%
“…In the second analysis, the authors investigated the relationship between WBC counts and thrombotic events. 16 Evaluable patients (N = 1565) were grouped into 1 of 4 cohorts based on the last WBC measurement taken during the study period before a thrombotic event or through the end of follow-up: (1) WBC < 7.0 × 10 9 /L, (2) 7.0 to 8.4 × 10 9 /L, (3) 8.5 to < 11.0 × 10 9 /L, or (4) ≥ 11.0 × 10 9 /L. Mean follow-up time ranged from 3.6 to 4.5 years among WBC count cohorts, during which 24.9% of patients experienced a thrombotic event.…”
Section: Blood Cell Counts and Thrombotic Events In The Veteran Popul...mentioning
confidence: 99%
See 2 more Smart Citations